L’émigration péruvienne en Espagne entre 1985 et 2017 : de la réalité à la fiction - Nicole Fourtané (Cahiers de Civilisation Espagnole Contemporaine)
This paper brings to light, first, the political and socioeconomic context of Peru and Spain to explain the extent of the migratory attraction of this country on the Peruvians. Until 2005, Spain offers favorable integration possibilities: regularization of illegals, obtaining possibility of Spanish nationality. From 2008 the crisis generates a return phenomenon in the native country but the migration does not dry up. After, we approach the typical profile of these migrants and, finally, we analyze the experienced migration from within by a Peruvian nameless throughout the novel Paseador de perros (2008) of Sergio Galarza: multiple jobs, integration difficulties, poor housing, ownership of the premises, loneliness, feeling of rejection, etc.